In vitro propagation of Paphiopedilum helenea Aver. - Thi Viet Nga, Cao; Thi Nhu Quynh, Nguyen; Quang Nam, Vu (Journal of Forestry Science and Technology, 2025)
Paphiopedilum helenae Aver. (Orchidaceae), commonly known as Helen’s Lady Slipper, is a native species of Vietnam and predominantly found in limestone mountain areas of the Northern regions such as Bac Kan and Cao Bang provinces. It is also distributed in Guangxi province of China. The species typically grows at elevations ranging from 600 to 1000 m above sea level, in a tropical monsoon climate with high humidity and low light conditions due to canopy coverage. Paphiopedilum helenae is classified as Critically Endangered (CR) in the Vietnam Red Data Book (2007) and listed under Appendix I of the CITES. The study demonstrated that sterilizing the seeds of Paphiopedilum helenae using alcohol in three successive steps is an effective method, achieving 94.4% sterilization rate and 88.9% germination rate of the sterilized seeds. The highest shoot proliferation of Paphiopedilum helenae is obtained on MS (Murashige and Skoog, 1962) medium supplemented with 3 mg/L BAP and 1 mg/L Kinetin, 30 g/L sucrose, and 7 g/L agar. Supplementing the MS medium with 2 mg/L NAA and 1 mg/L IBA resulted in the best rooting of Paphiopedilum helenae shoots. Preliminary results suggest the successful application of in vitro culture techniques for micropropagating Paphiopedilum helenae, offering a large-scale production of high-quality plantlets to meet the demand for cultivating this valuable species.